2008
DOI: 10.1371/journal.pone.0003045
|View full text |Cite
|
Sign up to set email alerts
|

Reverse and Conventional Chemical Ecology Approaches for the Development of Oviposition Attractants for Culex Mosquitoes

Abstract: Synthetic mosquito oviposition attractants are sorely needed for surveillance and control programs for Culex species, which are major vectors of pathogens causing various human diseases, including filariasis, encephalitis, and West Nile encephalomyelitis. We employed novel and conventional chemical ecology approaches to identify potential attractants, which were demonstrated in field tests to be effective for monitoring populations of Cx. p. quinquefasciatus in human dwellings. Immunohistochemistry studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
168
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 34 publications
4
168
0
Order By: Relevance
“…In addition to these sensilla responding to plant and human compounds, we recorded also from two functionally distinct classes of A1 sensilla. One houses ORNs sensitive to the insect repellent DEET, whereas the other type responded to a mosquito oviposition pheromone (MOP) (10,18).…”
Section: Fig 3 Analysis Of Bird-and Human-derived Odorants By Gc-eamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these sensilla responding to plant and human compounds, we recorded also from two functionally distinct classes of A1 sensilla. One houses ORNs sensitive to the insect repellent DEET, whereas the other type responded to a mosquito oviposition pheromone (MOP) (10,18).…”
Section: Fig 3 Analysis Of Bird-and Human-derived Odorants By Gc-eamentioning
confidence: 99%
“…Several OBPs have been isolated and cloned from Culex spp. (7)(8)(9), and CquiOBP1 has been mapped to a specific sensilla type on antenna, and functional studies showed binding of this OBP to semiochemicals involved in the chemical ecology of this mosquito species (10).…”
mentioning
confidence: 99%
“…Effective management of Culex mosquito populations may be achieved with oviposition attractants and other kairomones (3,4), because larval development is a particularly vulnerable point in their life cycle. These semiochemicals are detected by the antennae of female adults with sensilla housing odorant receptors (ORs) (5,6) and odorant-binding proteins (OBPs) (7)(8)(9), and these molecular targets can be used in reverse chemical ecology approaches (10) for the development of green chemistry-based strategies for insect vector management (8). Previously, we have isolated an OBP from the antennae of C. quinquefasciatus, CquiOBP1, which is highly expressed in trichoid sensilla involved in the detection of a mosquito oviposition pheromone (8), (5R,6S)-6-acetoxy-5-hexadecanolide (11) (hereafter referred to as MOP).…”
mentioning
confidence: 99%
“…Previously, we have isolated an OBP from the antennae of C. quinquefasciatus, CquiOBP1, which is highly expressed in trichoid sensilla involved in the detection of a mosquito oviposition pheromone (8), (5R,6S)-6-acetoxy-5-hexadecanolide (11) (hereafter referred to as MOP). CquiOBP1 bound MOP with high affinity at high pH but showed no affinity at low pH (8). OBPs essential role for odorant reception in C. quinquefasciatus has been demonstrated by RNA interference experiments in which reduction of CquiOBP1 expression led to lower sensitivity for the detection of oviposition attractants, including MOP (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation